2019
DOI: 10.1161/circulationaha.119.042685
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Risk Stratification and Efficacy of Sodium-Glucose Cotransporter-2 Inhibitors in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) are at increased risk of developing heart failure. Sodium-glucose cotransporter-2 inhibitors reduce the risk of hospitalization for heart failure (HHF) in patients with T2DM. We aimed to develop and validate a practical clinical risk score for HHF in patients with T2DM and assess whether this score can identify high-risk patients with T2DM who have the greatest reduction in risk for HHF with a sodium-glucose cotransporter-2 inhibitor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 22 publications
3
110
2
1
Order By: Relevance
“…Numerous studies have demonstrated the cardioprotective effects of NO-sGC-cGMP-PKG signaling. sGC stimulation can attenuate LV remodeling after myocardial infarction in mice (Frankenreiter et al, 2018;Berg et al, 2019), decrease extracellular matrix protein production in human cardiac fibroblasts following TGF-β stimulation, and attenuate vascular dysfunction in diabetic rats (Grontved et al, 2014). The eNOS transcriptional enhancer (AVE9488) improves cardiac remodeling after myocardial infarction (Fraccarollo et al, 2008) and platelet NO availability and hyperactivity in HF.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the cardioprotective effects of NO-sGC-cGMP-PKG signaling. sGC stimulation can attenuate LV remodeling after myocardial infarction in mice (Frankenreiter et al, 2018;Berg et al, 2019), decrease extracellular matrix protein production in human cardiac fibroblasts following TGF-β stimulation, and attenuate vascular dysfunction in diabetic rats (Grontved et al, 2014). The eNOS transcriptional enhancer (AVE9488) improves cardiac remodeling after myocardial infarction (Fraccarollo et al, 2008) and platelet NO availability and hyperactivity in HF.…”
Section: Discussionmentioning
confidence: 99%
“…23 Indeed, UACR level, even in the microalbuminuric range, was incorporated in a novel risk score for incident HF hospitalizations. 23 Notably, patients with higher risk scores were more likely to derive cardiovascular benefit from the sodium-glucose cotransporter 2 inhibitor dapagliflozin. 23 Indeed, even among those with prevalent HF but without diabetes, dapagliflozin has demonstrated cardiovascular benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of HF risk can be useful for both clinicians and people with T2D: for clinicians, it can support them in the choice of therapeutic and preventive strategies; and for individuals with T2D, it can be a motivation tool to adopt healthy lifestyle measures and to observe prescribed risk-modifying treatments. Risk scores for HF in T2D include the WATCH-DM (Weight [BMI], Age, hyperTension, Creatinine, HDL-C, Diabetes control [fasting plasma glucose], QRS Duration, MI and CABG) score which is a simple, user-friendly, integer-based risk score that calculates the 5-year risk of incident HF among people with T2D [ 72 ], the TIMI (Thrombolysis in Myocardial Infarction) Risk Score for Heart Failure in Diabetes (TRS-HFDM) which is a novel, integer-based clinical risk score for predicting hospitalization for HF in people with T2D that includes the risk predictors prior HF, history of atrial fibrillation (AF), CAD, estimated glomerular filtration rate (eGFR) and urine albumin-to-creatinine ratio [ 73 ], and the Brest score which is a clinical prediction score for HF diagnosis in the emergency care setting that includes 11 variables: age at least 65 years, seizure dyspnoea, night outbreak, orthopnoea, history of pulmonary oedema, chronic pulmonary disease, myocardial infarction, crackles, leg oedema, ST segment abnormality, atrial fibrillation/flutter on electrocardiography [ 74 ].…”
Section: Identifying Risk Of Hf In Diagnosed T2dmentioning
confidence: 99%